ANALISIS FAKTOR KEBERHASILAN PELAKSANAAN PROGRAM KETAHANAN PANGAN DI DESA SIMBANG KECAMATAN PAMBOANG KABUPATEN MAJENE - , Muhammad Sajidin; Saddam Husain Tamrin,; Nurdiyah, (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This research aims to determine the implementation of food program resilience in Simbang Village, Pamboang District, Majene Regency, the analysis used uses Sabatier's policy theory (1986: 268) that there are six main variables which further influence the success of an implementation, namely clear and consistent policy goals or objectives , Strong theoretical support in formulating policies, Process implementation has a clear legal basis, Commitment and membership of policy implementers, stakeholder support and stability of social, economic and political conditions. This research uses a qualitative descriptive analytical method, where data analysis includes open data collection based on general questions and information analysis, as well as writing short notes throughout the research. The results of this research show that the implementation of the food security program in Simbang village which is sourced from village funds in 2022 has been carried out well. Of the six key variables that influence the success of implementing the food security program in Simbang Village, namely, the fifth variable is related to dominant stakeholder support in determining the success of implementing the food security program in Simbang Village, where the Simbang Village Government receives full support from various community stakeholders so that the impact What is felt from the Community Food Security Program policy in the village is that the community is helped in strengthening food security.